Effects of Artisanal Refinery on the Environment, Public Health and Socio-Economic Development of Communities in the Niger Delta Region - Ikezam, P.; Elenwo, E. I.; Oyegun, C. U. (Environmental Management and Sustainable Development, 2021)
Nigeria discovered crude oil in 1956. Instead of making sustainable economic progress since, the country spiraled into serious economic waste and loss, due to pollution from crude oil, corruption, neglect of the oil producing regions and high handedness of the IOCs/NOCs. Today, not only are legitimate oil exploration pipelines leaking oil into the environment, illegal artisanal refineries are contributing to pollution problems and by extension economic and health effects. This study thus investigated, effects of artisanal refinery on the environment, public health and socio-economic development of communities in the Niger Delta Region. The cross-sectional research design was used in this study. The target population comprised of illegal bunkering/artisanal refining sites and households that dwell within the artisanal refinery sites. The Taro Yamane formula was used to determine the sample sizes for state and 400 was realized for each state. 1324 artisanal refining sites were determined and using Taro Yamane equation 313 sites were derived. The Kruskal-Wallis H test was used for data analysis. The study found that, locals complained about how artisanal refineries affected their environment, health and economics. These effects varied spatially based on the result of the Kruskal Wallis test at P<0.05. However, some of the locals identified that, despite the environmental pollution because of illegal artisanal refining in the area, some economic gains abound. It is therefore the position of this study that artisanal refining be improved, so that the environmental and health effects be reduced, while making room for sustainable economic development.